An Overview of High Thermal Conductive Hot Press Forming Die Material Development - A. R., Zulhishamuddin; S. N., Aqida (Faculty Mechanical Engineering, UMP, 2015)
Most of the automotive industries are using high strength steel components, which are produced via hot press forming process. This process requires die material with high thermal conductivity that increases cooling rate during simultaneous quenching and forming stage. Due to the benefit of high quenching rate, thermal conductive die materials were produced by adding carbide former elements. This paper presents an overview of the modification of alloying elements in tool steel for high thermal conductivity properties by transition metal elements addition. Different types of manufacturing processes involved in producing high thermal conductive materials were discussed. Methods reported were powder metallurgy hot press, direct metal deposition, selective laser melting, direct metal laser sintering and spray forming. E lements likes man ganese, nickel, molybdenum, tungsten and chromium were proven to increase thermal conductivity properties . Thermal conductivity properties resulted from carbide network presence in the steel microstructure. To develop feasible and low cost hot press formin g die material, casting of Fe - based alloy with carbide former composition can be an option. Current thermal conductivity properties of hot press forming die material range between 25 and 66 W/m.K. The wide range of thermal conductivity varies the mechanica l properties of the result ing components and lifetime of HPF dies.